Intersectional Feminist Insights into the Lived Experiences of Domestic Violence and Trauma in Marginalized Women - Sazgar, Raheleh (Université d'Ottawa | University of Ottawa, 2026)
Violence against women continues to be a pervasive social issue worldwide, including in Canada, with women from marginalized social locations often facing compounded forms of violence, exclusion, and systemic neglect (Kaur & Garg, 2008; Singhal et al., 2021; Sokoloff & Dupont, 2005; World Health Organization, 2021). Domestic violence (DV) is a potentially traumatic experience for many women, often resulting in serious physical and psychological consequences, including post-traumatic stress disorder (PTSD) (Goodman & Epstein, 2008). However, the experiences and meanings that marginalized women attribute to trauma and PTSD remain underexplored (Baird, 2018). This thesis addresses this gap by critically examining how women who have experienced domestic violence and received a PTSD diagnosis understand and give meaning to trauma, and how they experience interventions provided by domestic violence and mental health services. Guided by an intersectional feminist framework (Crenshaw,1991), the research views trauma and violence as socially and structurally situated phenomena shaped by power, inequality, and identity (Brown, 2017; Herman, 2015). Using a feminist phenomenological approach and interpretative phenomenological analysis (IPA), the study draws on in-depth, open-ended interviews with women from diverse marginalized backgrounds in Canada, including Indigenous women and those from rural, religious, disabled, and sexually diverse communities. The methodological focus on lived experience and meaning making allows women’s voices to guide the interpretation of trauma beyond clinical or diagnostic frameworks. The findings highlight that participants conceptualize trauma not solely as an individual psychological response but as an ongoing experience of social and structural harm embedded within systems of inequality. Women described coercive control as a persistent form of domination that extends beyond physical violence and is shaped by race, class, disability, sexuality, and geography. Participants’ interpretations of PTSD reveal tensions between clinical definitions and lived realities of trauma, often exposing gaps in service delivery and cultural understanding. This research contributes to feminist scholarship on trauma and domestic violence by foregrounding the lived experience of marginalized women and challenging dominant, medicalized understandings of PTSD. It offers insights that can inform culturally responsive, intersectional, and trauma- and violence- informed practices within domestic violence and mental health systems.
Keywords: Domestic violence; Coercive Control; Trauma; PTSD; Intersectionality; Marginalized women